Polish autonomous nationalism against the background of social movement theory - Pisarski, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of this article is to analyze autonomous nationalism as a new social movement. This current of nationalism, which emerged at the turn of the 20th and 21st centuries, is characterized by a radical rejection of liberal democracy, as well as the ideology of the New Left. As a result of the analysis of the published content, it was possible to conclude that autonomous nationalism is a formula of nationalism as a movement of resistance to the establishment, adapted to the conditions of the 21st century.
Keywords: autonomous nationalism; far right; new social movements; populism; anti-globalism